2017
DOI: 10.3390/jcm6040037
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Coenzyme Q10 Determination in Mitochondrial Patients

Abstract: Coenzyme Q10 (CoQ) is a lipid that is ubiquitously synthesized in tissues and has a key role in mitochondrial oxidative phosphorylation. Its biochemical determination provides insight into the CoQ status of tissues and may detect CoQ deficiency that can result from either an inherited primary deficiency of CoQ metabolism or may be secondary to different genetic and environmental conditions. Rapid identification of CoQ deficiency can also allow potentially beneficial treatment to be initiated as early as possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…At present, CoQ treatment monitoring is a matter of debate. CoQ distribution from the serum to cells and tissues after oral intake is not fully understood, and the best biological sample to monitor patients under CoQ supplementation is currently under discussion [ 6 ]. Furthermore, different CoQ formulations are available with potentially different bio availabilities, depending on whether the CoQ is in the oxidized or the reduced form and what excipients are used [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, CoQ treatment monitoring is a matter of debate. CoQ distribution from the serum to cells and tissues after oral intake is not fully understood, and the best biological sample to monitor patients under CoQ supplementation is currently under discussion [ 6 ]. Furthermore, different CoQ formulations are available with potentially different bio availabilities, depending on whether the CoQ is in the oxidized or the reduced form and what excipients are used [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are concerns about CoQ plasma measurements for diagnosis, since it seems to be influenced by the amount of plasma lipoproteins (carriers of CoQ in circulation) and the dietary intake. Muscle or fibroblasts represent the preferred diagnosis tissues, although sometimes fibroblasts do not show reduction while muscle does(129).It has been shown that white blood cells CoQ levels alone are not reliable to diagnose primary CoQ deficiency in the setting of nephrotic syndrome(76).…”
mentioning
confidence: 99%
“…In presence of variants of uncertain significance, functional and/or complementary studies are needed. Blood mononuclear cells represent a readily accessible sample, which is often suitable as an alternative to muscle for the measurement of CoQ 10 , by high performance liquid chromatography or mass spectrometry [11,58] . In contrast, plasma levels of CoQ 10 are influenced by the amount of plasma lipoproteins (carriers of CoQ 10 in circulation), dietary intake, or supplementation, therefore cannot be used for diagnostic purpose.…”
Section: Diagnosis Of Early Onset Multisystemic Phenotype Of Primary mentioning
confidence: 99%